Mechanism and Kinetics of Quenching of Quercetin on Photosensitizing Effect of Synthetic Food Colorant Erythosine in Palm Oil Oxidation - Posman sibuea; Sri Raharjo; Umar Santoso (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
The effect 0, 200, 400, 600, 800 and 1000 ppm (wt/vol) quercetin on the singlet oxygen oxidation of palm oil in methylene chloride containing 100 ppm erythrosine, were studied during storage under 400 lux fluorecent light for 5 h by measuring peroxide value. Steady-state kinetic approximation was used to determine the quenching mechanism and quenching rate constant of quercetin in the erythrosine-sensitized photo oxidation of palm oil. Erythrosine greatly increased the As photo oxidation of palm oil, as was expected. Quercetin was extremely effective at minimizing erythrosine-sensitized photo oxidation of palm oil. As the concentration of quercetin increased from 0 to 200, 400, 600, 800 and 1000 ppm, the peroxide value of palm oils decreased significantly (p